Application of Different Extraction Methods for Investigation of Nonmetallic Inclusions and Clusters in Steels and Alloys. (9th January 2014) - Janis, Diana; Inoue, Ryo; Karasev, Andrey; Jönsson, Pär G.
Abstract : The characterization of nonmetallic inclusions is of importance for the production of clean steel in order to improve the mechanical properties. In this respect, a three-dimensional (3D) investigation is considered to be useful for an accurate evaluation of size, number, morphology of inclusions, and elementary distribution in each inclusion particle. In this study, the application of various extraction methods (chemical extraction/etching by acid or halogen-alcohol solutions, electrolysis, sputtering with glow discharge, and so on) for 3D estimation of nonmetallic Al2 O3 inclusions and clusters in high-alloyed steels was examined and discussed using an Fe-10 mass% Ni alloy and an 18/8 stainless steel deoxidized with Al. Advantages and limitations of different extraction methods for 3D investigations of inclusions and clusters were discussed in comparison to conventional two-dimensional (2D) observations on a polished cross section of metal samples.